The Impact of Green Economy Initiatives at Universities on Student Expenditures: A Case Study of the Gridwiz E-Bike Program and Water Refill Station at Mataram University - Fiki Adrian; Diswandi (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study aims to analyze the impact of green economy implementation at Mataram University on student spending through the Gridwiz E-Bike and Water Refill Station (WRS) programs. This study uses a quantitative approach with a pre–post quasi-experimental design and comparison groups to measure the microeconomic impact of green campus initiatives. Data were collected from active students through a structured questionnaire covering variables of green economy implementation, student spending, student engagement, and financial literacy. Data were analyzed using Paired Samples T-test. Results show that the implementation of green economy programs contributes positively to student financial efficiency. The higher the intensity of E-Bike and Water Refill Station usage, the lower the monthly spending on transportation and bottled water consumption. This study provides empirical evidence that green campus initiatives not only support environmental sustainability but also improve student economic well-being, providing practical insights for universities to design sustainability policies aligned with the Sustainable Development Goals (SDGs).